2014
DOI: 10.1111/jop.12239
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics profiling of keratocystic odontogenic tumours reveals AIDA as novel biomarker candidate

Abstract: Immunohistochemical validation of chosen putative biomarkers revealed axin interaction partner and dorsalization-antagonist (AIDA), known as a protein that blocks activation of JNK signalling pathway, as a differential biomarker for KCOT lesions on an independent cohort of KCOT tissue samples in comparison with most prevalent intra-oseal lesions inflammatory odontogenic cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…In the present study, we investigated the proteomic profile of OKC using LC‐MS/MS method. In 2015, Malčić et al reported a comparative proteomic profiling of OKC, oral mucosa, and radicular cyst using LC‐MS/MS, but focusing on identifying potential biomarkers (Ivanišević Malčić et al., 2015). Fold‐calculation and downregulated proteins were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the proteomic profile of OKC using LC‐MS/MS method. In 2015, Malčić et al reported a comparative proteomic profiling of OKC, oral mucosa, and radicular cyst using LC‐MS/MS, but focusing on identifying potential biomarkers (Ivanišević Malčić et al., 2015). Fold‐calculation and downregulated proteins were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these studies, which have focused on specific genomic regions, genes or proteins, a few investigations have evaluated global molecular changes in OKCs. An analysis of OKC proteomics was carried out by comparing OKC lesions with patient‐matched normal oral mucosa . This study revealed 43 differentially expressed proteins in OKCs, including proteins involved in the JNK and p38 MAPK signaling pathways …”
Section: Genetic Alterationsmentioning
confidence: 99%
“…An analysis of OKC proteomics was carried out by comparing OKC lesions with patient‐matched normal oral mucosa . This study revealed 43 differentially expressed proteins in OKCs, including proteins involved in the JNK and p38 MAPK signaling pathways …”
Section: Genetic Alterationsmentioning
confidence: 99%